2018
DOI: 10.1007/s10334-018-0674-z
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and texture analysis of structural biomarkers using neighborhood-clustering-based level set in MRI of the schizophrenic brain

Abstract: A framework of geometric and Laws texture features obtained from brain subregions can be used as a supplement for diagnosis of psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The texture can also be seen as a similarity grouping in an image [2] or as natural scenes containing semi-repetitive arrangements of pixels [3]. In spite of the difficulty to give a precise definition of this notion, the analysis of texture is used in many applications: biomedical field (see [4]- [7]), industrial automation (see [8]- [10]), document image analysis (see [11]- [13]), remote sensing (see [14]- [16]), face recognition (see [17]) to cite only a few. These applications use texture parameters for classification, segmentation, or synthesis of images.…”
Section: Introductionmentioning
confidence: 99%
“…The texture can also be seen as a similarity grouping in an image [2] or as natural scenes containing semi-repetitive arrangements of pixels [3]. In spite of the difficulty to give a precise definition of this notion, the analysis of texture is used in many applications: biomedical field (see [4]- [7]), industrial automation (see [8]- [10]), document image analysis (see [11]- [13]), remote sensing (see [14]- [16]), face recognition (see [17]) to cite only a few. These applications use texture parameters for classification, segmentation, or synthesis of images.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific mechanisms involved in producing these structural deficits remain incompletely understood. In recent years, it has been consistently reported that SZ patients have structural abnormalities in the brain, including the middle temporal gyrus, middle frontal gyrus, thalamus, and corpus callosum (CcSum) [6][7][8]. e brain structure location and neurobiological processes underlying these structural abnormalities are central to the pathophysiology of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, optimized features are selected with binary particle swam optimization (BPSO) from whole‐brain region shows significant texture pattern change in SZ with Fuzzy SVM (FSVM) classifier . In addition, Laws texture feature identified a heterogeneous appearance in the brain stem, corpus callosum, and ventricular regions from SZ brain …”
Section: Introductionmentioning
confidence: 99%
“…23 In addition, Laws texture feature identified a heterogeneous appearance in the brain stem, corpus callosum, and ventricular regions from SZ brain. 24 The aim of the proposed work is to study the neuroanatomical and textural variations from cerebellum region in SZ and SA brain MR images based on radiomic features. Initially, level set based on shape constraint is used to segment cerebellum region from MR images.…”
Section: Introductionmentioning
confidence: 99%